The Impact of Cough Etiquette Education and Effective Cough Training on Increasing the Knowledge of Students at Elementary School 03 Pengasinan, Depok - Febriani, Nelly; Fadila, Nazma Putri; Putri, Irly Aisyah; Arisma, Sari; Ratnasari, Ajeng Ayu; Pramesty, Syarla Bella Dewi; Aulia, Della Zahra; Erlingga, Maurine Rivalda; Chairunisa, Khanza Hanaya; Napitupulu, Friskila Novelia; Syachfitri, Zellda Nur (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Respiratory tract infections remain a common health problem in school environments and carry a high risk of transmission, thereby necessitating education on cough etiquette and effective coughing techniques as preventive measures. This study aims to evaluate the effectiveness of providing education on cough etiquette and effective coughing in improving the knowledge of elementary school students. This research employed a descriptive qualitative approach, with data collected through observation, pre-test, post-test, and demonstrations to assess changes in students understanding before and after the educational intervention. The results showed a significant increase in post-test scores, marked by a higher number of students selecting the agree and strongly agree categories across all statement items, indicating that the educational activity contributed to improving students knowledge regarding proper cough etiquette and effective coughing techniques. These findings suggest that the implemented health education has the potential to support efforts in reducing the transmission of respiratory infections within school settings.